The Relationship Between Nutrition Knowledge and Dietary Intake of University Students: A Scoping Review - Michelle O’Leary; Elaine Mooney; Amanda McCloat (Dietetics, 2025)
This study aimed to provide an overview of published studies that assess the relationship between nutrition knowledge and dietary intake among university students. A scoping review was undertaken and articles assessing the relationship between nutrition knowledge and dietary intake among university students were identified. EMBASE, PsycINFO and Scopus were searched for peer-reviewed articles reporting primary research. The initial search generated 805 potentially relevant articles. After reviewing titles and abstracts and applying the exclusion criteria, 22 articles were deemed eligible for inclusion. Nutrition knowledge was measured in all studies and information was predominantly collected using adapted General Nutrition Knowledge Questionnaires (GNKQs). Dietary intake measurement methods varied across the studies, with the Food Frequency Questionnaire (FFQ) being commonly used. Findings identified that in most studies a positive relationship was found between nutrition knowledge and dietary intake. The ability to draw strong conclusions about the relationship between nutrition knowledge and dietary intake in university students is limited by the heterogeneity of the study design, the subpopulations considered, and the tools used. Notwithstanding this, findings indicate that the majority of studies reported a positive relationship between nutrition knowledge and dietary intake. Future studies should consider the use of validated assessment tools for both nutrition knowledge and dietary intake and the inclusion of more male student participants.